'Making narrative portraits: a methodological approach to analysing qualitative data'. Issue 6 (1st November 2020) - Rodríguez-Dorans, Edgar; Jacobs, Paula
ABSTRACT: This paper proposes the method of 'narrative portraiture', which, located within the wider field of narrative studies, offers an analytical tool to narrative data. Two research projects, one on disability and one on identity, are used to illustrate how the method can be applied. While the paper will focus on the methodological benefits and limitations of the approach, throughout the article we also highlight the ethical concern of representation. We suggest that through 'narrative portraiture' research findings can be contextualised in broader social narratives without losing sight of the unique personal qualities of the research encounter. Thus, we argue for the importance of bringing the participant and their everyday life experience into focus, highlighting that a portrayal of a sole story can be, not only a medium to understand a research phenomenon, but also a valuable research output in itself.